2011
DOI: 10.1111/j.1365-2699.2011.02512.x
|View full text |Cite
|
Sign up to set email alerts
|

Body size clines in the European badger and the abundant centre hypothesis

Abstract: Aim  To test the abundant centre hypothesis by analysing the physical and climatic factors that influence body size variation in the European badger (Meles meles). Location  Data were compiled from 35 locations across Europe. Methods  We used body mass, body length and condylo‐basal length (CBL) as surrogates of size. We also compiled data on latitude, several climatic variables, habitat type and site position relative to the range edge. We collapsed all continuous climatic variables into independent vectors u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 73 publications
(155 reference statements)
1
17
0
Order By: Relevance
“…The abundant center hypothesis, which predicts that body size and abundance will be greater in the center of an organism's distribution than at the edges (e.g., Samis & Eckert 2007, Virgos et al 2011, agrees with our observations of body size variation, which showed a trend of increase with increasing elevation (a proxy for distance from the coast) rather than a general south to north increase as predicted by Bergmann's rule. Regarding abundance, orthopterists reported O. superbum to be rare at the type locality in New Jersey (Rehn & Hebard 1915) and elsewhere along the Atlantic and Gulf Coasts (T.J. Walker and G.K. Morris, pers.…”
Section: Discussionsupporting
confidence: 81%
“…The abundant center hypothesis, which predicts that body size and abundance will be greater in the center of an organism's distribution than at the edges (e.g., Samis & Eckert 2007, Virgos et al 2011, agrees with our observations of body size variation, which showed a trend of increase with increasing elevation (a proxy for distance from the coast) rather than a general south to north increase as predicted by Bergmann's rule. Regarding abundance, orthopterists reported O. superbum to be rare at the type locality in New Jersey (Rehn & Hebard 1915) and elsewhere along the Atlantic and Gulf Coasts (T.J. Walker and G.K. Morris, pers.…”
Section: Discussionsupporting
confidence: 81%
“… They are territorial central place foragers that utilize fixed burrows (‘setts’) that are critical for their survival (Byrne et al ., ; Noonan et al ., ) – consequently, they do not migrate in response to changing conditions. Their body weight fluctuates naturally across seasons, coupled with changes in activity within temperate and northern latitudes (Kowalczyk et al ., ; Noonan et al ., ). There is substantial literature linking badger population dynamics to weather conditions (Nouvellet et al ., ), trends in climate (Macdonald & Newman, ), patterns of weather variability (Macdonald et al ., ) and energetics (Noonan et al ., ) – capable of influencing their biogeographical distribution (e.g. Bevanger & Lindstrom, ; Virgós et al ., ), all substantially relating to their diet – in particular, a preference for earthworms (Kruuk & Parish, ; Johnson et al ., ; Cleary et al ., ). Badger distributions and regional abundances are subject to various management (culling) strategies in response to their role as a host species for Mycobacterium bovis, the causative agent of bovine tuberculosis (bTB), linked to cattle herd bTB risk epidemiology (Donnelly et al ., ; Griffin et al ., ; Byrne et al ., ). …”
Section: Introductionmentioning
confidence: 99%
“…Baboon size and shape are undoubtedly spatially variable, but it is not clear whether this variation has arisen in response to environmental pressures, as has been argued to be the case in other instances of clinal variation (James, ; Burnett, ; Ferguson & Larivière, ; Virgós et al. ). This seems likely in baboons as they are extremely responsive to the environment, which modulates group size (Byrne et al.…”
Section: Introductionmentioning
confidence: 99%